Control of Metal–Organic Framework Crystallization by Metastable Intermediate Pre‐equilibrium Species. (7th December 2018) - Yeung, Hamish H.‐M.; Sapnik, Adam F.; Massingberd‐Mundy, Felicity; Gaultois, Michael W.; Wu, Yue; Fraser, Duncan A. X.; Henke, Sebastian; Pallach, Roman; Heidenreich, Niclas; Magdysyuk, Oxana V.; Vo, Nghia T.; Goodwin, Andrew L.
Abstract: There is an increasing amount of interest in metal–organic frameworks (MOFs) for a variety of applications, from gas sensing and separations to electronics and catalysis. However, the mechanisms by which they crystallize remain poorly understood. Herein, an important new insight into MOF formation is reported. It is shown that, prior to network assembly, crystallization intermediates in the canonical ZIF‐8 system exist in a dynamic pre‐equilibrium, which depends on the reactant concentrations and the progress of reaction. Concentration can, therefore, be used as a synthetic handle to directly control particle size, with potential implications for industrial scale‐up and gas sorption applications. These findings enable the rationalization of apparent contradictions between previous studies of ZIF‐8 and opens up new opportunities for the control of crystallization in network solids more generally.